Body, colors and emotions in Buenos Aires: an approach from social sensibilities - Scribano, Adrián Oscar (2012)
We live in a permanent relationship between what our bodies tell us and what we have socially apprehended. This paper aims to show some features of social sensibilities in inhabitants of BsAs city linking their everyday bodily experiences, colors they attribute to the body, and parts of the body in which they say they experience their sensations. Based on a 2010 survey, interpretative patterns concerning color, body, and emotions are suggested. First, the theoretical starting point for connecting colors, emotions, bodies, and daily life is reviewed. Some results of the study mentioned regarding the issue addressed are summarised. Finally, an interpretation of the findings is displayed, evidencing connections of ways of experiencing the body in terms of colors and emotions.